Association between computed tomography-derived tricuspid annular dimensions and prognosis: insights from whole-beat computed tomography assessment. (19th July 2021) - Hirasawa, Kensuke; Fortuni, Federico; van Rosendael, Philippe J; Ajmone Marsan, Nina; Bax, Jeroen J; Delgado, Victoria
Abstract: Aims: Tricuspid regurgitation (TR) has been associated with outcome in patients treated with transcatheter aortic valve implantation (TAVI). Tricuspid annulus (TA) dimensions are associated with TR. However, the TA is highly dynamic during the cardiac cycle, and the interaction between the TA dimensions, TR, and patient prognosis has never been evaluated. This study aimed to characterize the dynamics of the TA along with the cardiac cycle and its association with prognosis in patients undergoing TAVI. Methods and results: Patients with severe aortic stenosis who underwent whole-beat computed tomography ( n = 393, mean age 80 ± 7 years, 53% male) were included. The ratio between anterior-posterior (AP) and septal-lateral (SL) diameter of the TA was calculated at end-systole (ES), mid-diastole (MD), and end-diastole (ED) to characterize the TA shape throughout the cardiac cycle. The primary endpoint was all-cause mortality. During a median follow-up of 3.6 (1.7–5.5) years, 146 patients died. While all the TA parameters at ES and MD were not associated with all-cause mortality, a low AP/SL ratio at ED (more circular geometry) was independently related with all-cause mortality (hazard ratio: 4.717, 95% confidence interval: 1.481–15.152; P = 0.009). In addition, a more circular TA shape at ED (AP/SL ratio < 1.20) was also associated with more right atrial and ventricular dilation, more frequently significant TR, and a higher prevalence of atrial fibrillation. Conclusion: Circular remodelling of the TA shape at ED is associated with more right atrial and ventricular dilation, and a higher long-term mortality after TAVI. The evaluation of the TA shape at ED may be a useful parameter in the risk stratification of patients undergoing TAVI.